Characterisation of rice fallow period for increasing cropping intensity in Khordha district of Odisha - S. PATTANAYAK; B.S. RATH; S. PASUPALAK; A.K.B. MOHAPATRA; A. BALIARSINGH; A. NANDA; G.S. PANIGRAHI (Journal of Agrometeorology, 2019)
The possibility of increasing the cropping intensity in Khordha district was assessed by block-wise characterisation of rainfall, soil texture, available water holding capacity of soil and district level temperature during the rice fallow period as well as deciding the appropriate sowing window for both kharif and rabi crops. More than 50% chances of occurrence of wet weeks at the beginning of the kharif season (20-22 SMW) indicated that the summer ploughing and initial seed bed preparation could be taken up during the period followed by sowing of rice from 23 SMW. The 42-43 SMW with greater than 30% initial probability of wet week at 20 mm threshold limit. Considering the length of growing period (LGP) available, the adjustment of rice variety duration by 10-15 days in medium land and advancement of pulse sowing almost by 15 days before harvest of the rice crop (Pira crop) in low land was registered as the best su  suitable option for rabi pulses to ensure better utilisation of rice fallow. In addition to these, harvesting surplus water during kharif and storing in farm ponds for judicious utilisation during rabi season further enhanced the possibility of utilisation of rice fallow and increasing the cropping intensity. In the event of delayed monsoon the rice duration has to be adjusted accordingly not to sacrifice the designated suitable period for rabi pulses.